The Effects of Green Human Resource Management Practices on Sustainable Universities through Green Psychological Climate of Academic and Non-Academic Staff - Wajidi, Faraz Ahmed; Khan, Durre Shahwar; Khan, Nasir Ali; Syed, Muhammad Irfan (ACADEMIA International Journal for Social Sciences, 2025)
This research paper investigates the role of Green Human Resource Management (GHRM) practices in promoting sustainable development within university settings. Specifically, it examines how the implementation of environmentally-focused HR policies and initiatives can influence the perceptions and attitudes of both academic and non-academic staff, through the mediating effect of the Green Psychological Climate (GPC) — a shared perception among employees that the organization values and supports environmentally responsible behaviors. The study aims to understand the pathways through which GHRM shapes the organizational climate and, subsequently, drives sustainable university performance across multiple dimensions such as resource efficiency, waste reduction, and eco-friendly campus initiatives. Using a quantitative research design, the study collected and analyzed data from a diverse sample of university employees representing various faculties and administrative departments. Survey instruments measured the extent of GHRM practices, the strength of the GPC, and indicators of sustainable outcomes within the institution. Statistical analysis, including mediation testing, was employed to assess the relationships among these variables. The findings reveal a significant positive correlation between the adoption of GHRM practices and the perception of a green psychological climate. Moreover, GPC was found to be a crucial mediator that enhances the impact of GHRM on the university’s sustainability performance. The analysis also uncovered notable differences between academic and non-academic staff: academic personnel demonstrated a stronger alignment with and responsiveness to GHRM initiatives, suggesting that their engagement may be pivotal for advancing institutional sustainability goals. These insights point to the importance of developing tailored HR strategies that consider the unique motivational factors and work contexts of different employee groups. Overall, this study contributes to the growing body of knowledge on sustainable management in higher education by highlighting the interplay between HR policies, organizational climate, and environmental outcomes. It offers practical recommendations for university administrators and policymakers aiming to embed sustainability into the institutional culture by leveraging employee engagement and fostering a supportive green work environment.